Bioelectrochemical system for landfill leachate treatment – challenges, opportunities, and recommendations. Issue 6 (1st November 2016) - Shehzad, Areeb; Bashir, Mohammed J. K.; Sethupathi, Sumathi; Lim, Jun-Wei; Younas, Muhammad
Abstract: Increasing awareness of the energy–environment centers leads to the development of new technologies that have a direct impact on energy production and consumption during environmental remediation. Bioelectrochemical system (BES) is anticipated to be the emerging technology for the simultaneous removal/recovery of resources such as energy, nutrients, water, and heavy metals. Organic compounds inside the leachate are oxidized by micro-organisms which in turn lead to the production of energy and other value-added resources. Through the integration of membrane process such as forward osmosis in BES will help to recover the high-quality water for applications like agricultural. Recovery of metals is largely affected by uncertainty in concentration but still recovery of metal is achievable in leachate. Phosphorous and ammonia can be recovered through cathode reduction reactions driven by electricity generation. Low bioavailability of landfill leachate is one of the major challenges for BES which can be improved through proper pretreatment of landfill leachate. Another challenge of achieving the metal recovery from leachate is the low concentration of heavy metals. System scaling up remains as a great confront, especially for BES as energy production and consumption balance needs to be well understood. This review paper identified the key challenges, opportunities, and future recommendations for the recovery of resources from leachate using BES.